"We Live From Mother Nature": Neoliberal Globalization, Commodification, the "War on Drugs, " and Biodiversity in Colombia Since the 1990s. (3rd August 2015) - Chaves-Agudelo, J. Marcela; Batterbury, Simon P. J.; Beilin, Ruth
This article explores how macroeconomic and environmental policies instituted since the 1990s have altered meanings, imaginaries, and the human relationship to nature in Colombia. The Colombian nation-state is pluri-ethnic, multilingual, and megabiodiverse. In this context, indigenous peoples, Afro-Colombians, and some peasant communities survive hybridization of their cultures. They have developed their own ways of seeing, understanding, and empowering the world over centuries of European rule. However, threats to relatively discrete cultural meanings have increased since major changes in the 1990s, when Colombia experienced the emergence of new and modern interpretations of nature, such as "biodiversity, " and a deepening of globalized neoliberal economic and political management. These policies involve a modern logic of being in the world, the establishment of particular regulatory functions for economies, societies, and the environment, and their spread has been facilitated by webs of political and economic power. We trace their local effects with reference to three indigenous groups.